Funções da preposição “de” no uso do português brasileiro - Lião, Graziela Bonato (2019)
This dissertation is located in the area of Portuguese language grammar and has as its theme the diferent functions wich the preposition OF acquires in the effective usage of Brazilian Portuguese. The initial hypothesis is that in the effective usage of the Brazilian Portuguese, the preposition OF is a lexeme and/or gramema. The research done is justified, since the traditional Grammar in Brazil defines the prepositions as a class of words that relates word to word. The Dictionary of Portuguese Uses, DUP, by Francisco da Silva Borba (2002), the starting point of the research, presents the preposition OF as a term containing a series of predications, in order to consider this preposition as lexeme, capable of receiving grammaticalizations. It is based on the systemic-functional grammar of Givón (1993), in the effective use of the language, when the systemic units, pancronically, acquire functions. The general objective of this work is to contribute with the gramatical studies of Brazilian Portuguese and specific objectives are: I. review treatments data from historical grammar and traditional grammar to preposition OF; II. to seek, through the diachrony oh the Portuguese Language, the presente panchronic uses of the preposition OF; III. to examine the uses of the preposition OF in segments of written texts, in search of lexical function; IV. to examine the uses of the preposition OF in segments of written texts, in search of grammatical function. The research carried out is of a qualitative nature, with a selected corpus by Mário Viana and Ivan Angelo chronicles, published in the magazine Veja São Paulo, and several texts, published in the São Paulo magazine, Folha de S. Paulo, and also in the journal Claudia, with several authors, collected between 2017 and 2018. The results show that this is a hybrid term, functioning both as a lexeme and as a grammar. As lexeme establishes the relation between words, inserting meanings according to the contexts in which it appears. As a grammar it is an independent grammatical morpheme that functions in the relationship between lexias